Information portal for women's organization / Emmy Jong Ee Mei - Emmy , Jong Ee Mei (2003)
This report describes the proposed Information Portal for Women's Organization developed for the PELITAWANIS TNB Organization, a women's organization established by Tenaga Nasional Berhad (TNB) to foster closer ties between the women work force and wives of the employees from all levels in TNB. The PELITAWANIS TNB Portal is for use by the members of the PELITAWANIS TNB Organization.This portal is a one-person project handled by the author. Therefore, the author is responsible for the development of all the system module. Among the modules are search facilities, online, registration, forum, bulletin board, member list and update, and user feedback. The purpose of this portal is to present information regarding the organization, its activities, members and services in an interesting manner and to make this information readily available to its members and other interested parties. It also facilitates information sharing besides encouraging interaction and communication between members. The portal also servesas an avenue for announcements regarding the organization. Other than that, it will also be possible to monitor the log ins of the members. The administrators of the portal can perform management tasks to update the contents of the portal and the member data. The Waterfall with Prototype model is chosen as the development platform is the Microsoft SharePoint Portal Server. The PELITAWANIS TNB portal of course will also undergo testing and evaluation after its completion. With the birth of the portal, its is hoped that this will encourage more women to use the facilities made available to enrich their knowledge and experience, particularly in the areas of information and communication technology.